1986
DOI: 10.5432/jjpehss.kj00003392239
|View full text |Cite
|
Sign up to set email alerts
|

A new test for controllability of motor imagery: the examination of its validity and reliability

Abstract: Controllability of motor imagery is one of the critical faCtors for the effectiveness of mental praCtice . ・lt ・i ・ generally ・d・fin ・d ・・ th・ ・bility ・t・ c ・nt ・・1 ・・ 剛 p ・1 ・t・ m ・t・・ im・gery m ・・ t・lly ・ 1・ this

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…One such test is the Controllability of Motor Imagery test (Nishida et al 1986), which athletes have been shown to perform better on (Naito 1994). Note, however, that using the definitions proposed to address Hurdle #1, this questionnaire is a test of movement imagery, rather than motor imagery, as it uses a third-person perspective Ideally, future research would first measure an individual's motor imagery ability prior to the actual task of interest, as individual differences in ability and therefore BOLD response during the fMRI study.…”
Section: Proposed Solutionsmentioning
confidence: 99%
“…One such test is the Controllability of Motor Imagery test (Nishida et al 1986), which athletes have been shown to perform better on (Naito 1994). Note, however, that using the definitions proposed to address Hurdle #1, this questionnaire is a test of movement imagery, rather than motor imagery, as it uses a third-person perspective Ideally, future research would first measure an individual's motor imagery ability prior to the actual task of interest, as individual differences in ability and therefore BOLD response during the fMRI study.…”
Section: Proposed Solutionsmentioning
confidence: 99%
“…The Controllability of Motor Imagery (CMI) test was adapted following the idea of Nishida et al (1986) (Schott, 2004). This test evaluates the ability to supplement, transform, and reconstruct one's internally visualized body schema voluntarily in response to verbal instructions for movement of sequential body parts (arm, leg, torso, head).…”
Section: Motor Imagery-generation and Controllabilitymentioning
confidence: 99%
“…Vividness is often measured via introspective reports through validated questionnaires (i.e., Movement Imagery Questionnaire [MIQ]; Hall & Martin, 1997). An interesting alternative to assess controllability and generation is the Controllability of Motor Imagery Scale (CMI; Nishida et al, 1986;Schott, 2004), where subjects follow a series of instructions each specifying a single mental movement of a limb; at the end the subject must assume the position produced by the combination of movement. A semi objective method that is often used is mental chronometry.…”
mentioning
confidence: 99%
“…The experimenter can give a score only when entire body configuration is correct, and hence the f ull score after all questions is 15. The validity and reliability of this test were caref ully evaluated by Nishida et al (1986). As shown by Nishida et al (1986) and Naito (1994), gymnasts and subjects doing sports (football, volleyball, etc.…”
Section: Psychophysical Experimentsmentioning
confidence: 99%
“…The validity and reliability of this test were caref ully evaluated by Nishida et al (1986). As shown by Nishida et al (1986) and Naito (1994), gymnasts and subjects doing sports (football, volleyball, etc. ), who are generally good at imagining their body parts, showed higher scores when compared with subjects who did not do any sport.…”
Section: Psychophysical Experimentsmentioning
confidence: 99%